Rapid Detection of Powassan Virus in a Patient With Encephalitis by Metagenomic Sequencing. (13th September 2017) - Piantadosi, Anne; Kanjilal, Sanjat; Ganesh, Vijay; Khanna, Arjun; Hyle, Emily P; Rosand, Jonathan; Bold, Tyler; Metsky, Hayden C; Lemieux, Jacob; Leone, Michael J; Freimark, Lisa; Matranga, Christian B; et al.
Abstract: We describe a patient with severe and progressive encephalitis of unknown etiology. We performed rapid metagenomic sequencing from cerebrospinal fluid and identified Powassan virus, an emerging tick-borne flavivirus that has been increasingly detected in the United States.